Factors influencing coping skills of middle-aged adults in COVID-19, South Korea - Gu, Minkyung; Woo, Heeyoung; Sok, Sohyune (Frontiers in Public Health, 2024)
Background: In light of the persistent COVID-19 pandemic, there arises a compelling imperative to enhance the COVID-19 coping capacity among middle-aged adults within the South Korean population. Consequently, there is need for further research endeavors in this area. Objective: This study aims to explore and identify the factors influencing coping skills of middle-aged adults in COVID-19, South Korea. Methods: This study used a cross-sectional descriptive design. Participants were 147 middle-aged adults living at Seoul, Geounggi-do, and Chungchung-do in South Korea. Data included demographics, coping skills, impact of event, perceived health status, psychological well-being, and family support. The data was analyzed using SPSS Statistics 25.0 program. Data were collected from March to July, 2020. Results: The regression model was significant (F = 13.56, p < 0.001), and the adjusted R-squared representing the explanatory power of the model was 0.63. The strongest predictor was perceived health status (β = 0.34), followed by family support (β = 0.31), impact of event (β = -0.24), underlying disease (β = -0.13), and economic status (β = 0.11). Conclusions: This study suggests that to improve the coping skills of middle-aged adults in COVID-19, their perceived health status and family support should be strengthened, and impact of event should be decreased. Also, it needs that underlying disease are managed, and economic status is improved. Nurses need to pay more attention to the influencing factors to improve the coping skills of middle-aged adults in COVID-19, South Korea.